Experimental Evaluation of the Feasibility and Reproducibility of a Novel Multi-step Forming Process for Cu-OFE Micro Gear Manufacturing Compared to Macro-scale Forming - Rohrmoser, Andreas; Kraus, Martin; Leicht, Miriam; Merklein, Marion (Manufacturing Letters, 2022)
The increasing miniaturization of technical systems leads to a rising demand for micro components. Miniaturized drive systems with geared micro parts or micro gears are applied in various industries. Due to the demand for high production volumes, productive and resource-efficient fabrication is of major importance. Compared to industrially applied manufacturing methods like cutting and metal powder injection, cold forming provides technological, economic and ecological potential for the mass production of micro gears. It enables high productivity and advantageous mechanical properties of the gears. In the macroscopic size range, forming processes are well established in series production of gears. However, in micro-scale, according to the current state of the art, cold forming of modules m < 0.2 mm is not possible due to size effects, high tool loads and handling problems. Within this contribution, a multi-stage forming process for the fabrication of micro gears with a module of m = 0.1 mm is introduced and compared with a conventional forming process on macro-scale with a module of m = 1.0 mm. The use of coil material provides potential for easy handling of the micro parts in a progressive die for the potential application in a high-speed press. In addition, the multi-stage forming achieves a grain alignment, which enhances the formation of the micro gear profile. Based on the comparison between micro- and macro-scale, the performance of the micro process is analyzed with regard to deviations of process force as well as gear quality and possible size effects are identified. The results prove the feasibility of the process chain and the achievement of equivalent part quality and reproducibility compared to macro-scale forming.<br

Experimental study of the potential for extending the process limits in multi-stage forming of micro gears from sheet metal by a local short-term laser heat treatment - Leicht, Miriam; Kraus, Martin; Rohrmoser, Andreas; Merklein, Marion (Materials Research Proceedings 2023, 2023)
Cold forming of micro gears is currently not possible for modules m < 0.2 mm due to the occurrence of high tool stresses, handling problems and size effects. A multi-stage process chain of micro bulk forming from sheet metal offers the potential to solve these challenges. However, the industrial applicability is limited due to material efficiency. Against this background, the aim of this research work is an improvement of the material utilization as well as a further reduction of the tool stresses. Therefore, the influence of different heat treatment strategies as well as the materials copper Cu-OFE and brass CuZn30 are analyzed. Thus, a local laser heat treatment and a global heat treatment of the blanks are investigated. The focus of this research work is on the first process stage, pin extrusion, which is used for forming of the wheel blank. Since this process setup provides the material for the further forming stages, it has a huge influence on the material efficiency and on the forming of the gearing in the second process stage. Therefore, the component and process properties are evaluated to assess the influence of the measures. The results prove higher material efficiency at a similar tool stress by using local short-term heat treatmen

Influence of material in sheet-bulk metal forming from coil - Leicht, Miriam; Merklein, Marion (Production Engineering, 2024)
Sheet-bulk metal forming (SBMF) represents an innovative approach for the efficient manufacturing of functional integrated parts from sheet metal by applying bulk forming processes to sheet metal. It combines the advantages of part weight optimization and process chain shortening. In view of the increasing demand for functionally integrated components, the forming from coil offers an economical possibility to produce high output rates. Nevertheless, an underfilling of functional elements as well as an asymmetric part forming are current challenges. In order to apply SBMF from coil in industrial contexts, it is necessary to understand the causes of these process limits and to develop measures for improving the forming of functional elements and thereby push existing forming limits. In this paper, both a lateral and a backward extrusion process from coil for the forming of internal and external geared SBMF parts are investigated to develop a fundamental process understanding. In a combined numerical-experimental approach, the influence of the flow behavior of different materials as well as the impact of the main material flow direction of the process on the dimensional part accuracy is analyzed. This enables the evaluation of fundamental material-related dependencies and influences regarding the geometrical part accuracy, the mechanical component properties and the tool load for forming of the conventional deep-drawing steel DC04 (t0 = 2 mm), a high-strength steel material (HC260LA) and an aluminum alloy (AA6082 T6). Based on these findings, measures for material flow control are identified and investigated to counteract the challenges of SBMF from coil. These findings permit the identification of potential transferability of the identified cause-effect mechanisms to different processes, component geometries and materials. Thereby, in particular, an increase in coil width as well as lower a strain hardening behavior of the material offers the possibility to improve the geometrical accuracy of the components.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Cold Forming; Extrusion; Sheet-bulk metal forming

Investigation of Measures for Material Flow Control for a Backward Extrusion of Geared Components from Coil - Leicht, Miriam; Henneberg, Johannes; Merklein, Marion (Lecture Notes in Mechanical Engineering, 2024)
Increasing ecological and economic demands are setting new requirements for industrial manufacturing processes and components. The use of functional integration as a strategy of lightweight design offers the possibility to meet these requirements. However, a high functional integration implies an increasing component complexity, which challenges conventional forming processes to their limits regarding formability and efficiency. The novel process class of sheet-bulk metal forming (SBMF) offers the opportunity to combine the advantages of sheet metal and bulk forming by applying bulk forming operations to sheet metal semi-finished products. SBMF from coil offers further economic and ecological benefits through high output rates, short process times by eliminating costly handling tasks and a greater material efficiency. However, forming from coil also poses coil-specific challenges such as anisotropic material flow and reduced geometric part accuracy. Against this background, in this study, a backward extrusion process from coil for forming geared functional components is investigated on a high-speed press. The objective of this study is to analyze measures for a targeted material flow control in order to avoid unequal material flow and to improve part accuracy. Therefore, the mild deep drawing steel DC04 with an initial sheet thickness of 2.0 mm is analyzed in a combined numerical-experimental approach. Within these investigations, the influences of coil width, friction and feed width are analyzed and evaluated based on component and process parameters. Finally, measures for a purposive material flow are derived.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Cold forming; Extrusion; Sheet-bulk metal forming

Investigation of the influence of material and sheet thickness on a three-stage process chain for cold forming of micro gears with a module of 0.1 mm - Leicht, Miriam; Rohrmoser, Andreas; Kraus, Martin; Merklein, Marion (The 19th International Conference on Metal Forming (MF 2022), 2022)
In many industries, there is a trend towards miniaturization of technical components, such as drive systems, which enable the solution of high-precision positioning tasks because of their low volume and high dynamics. Geared micro parts are currently mainly produced by cutting and LIGA processes, but in mass production cold forming offers ecological and economic benefits. However, the cold forming of micro gears is restricted to a lower module limit of m = 0.2 mm due to high tool stresses, size effects and handling difficulties. To solve these challenges, in this contribution a three-stage forming process chain for the manufacturing micro gears (m = 0.1 mm) is investigated. In the first stage, a pin as wheel blank is extruded from sheet metal, which is geared subsequently by lateral extrusion. Finally, the micro gear is separated from sheet by shear cutting. The aim of this study is to demonstrate the applicability of the process chain for the materials Cu-OFE and CuZn30. In addition, the influence of the sheet thickness, which has a major impact on the forming process and the material efficiency, is analyzed. The geometrical and mechanical component properties as well as the machine data are evaluated to assess the variable

Novel process chain for forming micro gears with a module of 0.1 mm – Potentials and approaches for extending process limits - Leicht, Miriam; Merklein, Marion (Journal of Manufacturing Processes, 2025)
Micro gears are considered essential components of micro drive systems, which offer great potential for medical technology, measurement technology and robotics due to their small dimensions and their precise and highly dynamic transmission of movements and forces. However, established manufacturing processes such as hobbing, lithography technology or micro powder injection moulding are too time-consuming and cost-intensive for mass production. Therefore, new technological approaches are required. A multi-stage process chain of micro bulk forming from sheet metal offers great potential for the mass production of high-performance micro gears. In the first stage, a pin is extruded from sheet metal. Afterwards, the pin is geared by lateral extrusion, which is subsequently separated from sheet by shear cutting. The objective of this research work is to gain a fundamental understanding of the potentials and limitations of a multi-stage process chain for the production of micro gears with a module of m = 0.1 mm. The obtained knowledge serves as foundation for the development and analysis of approaches to overcome existing process limitations in terms of material efficiency and tool stress. The experimental results reveal, that a local adjustment of the material properties in the forming zone as well as a tool-sided limitation of the material flow radially outwards are suitable for improving the material efficiency.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Cold forming; Micro forming; Micro gear; Size-effect

Numerical and experimental investigation of a backward extrusion process for forming geared components from coil - Leicht, Miriam; Henneberg, Johannes; Merklein, Marion (Materials Research Proceeding, 2023)
Stricter political regulations, increasing ecological awareness of society as well as the pursuit for higher performance of components motivate lightweight construction. Functional integration is one way to realize lightweight design, resulting in increased demands on component geometry. Sheet-bulk metal forming (SBMF) offers the potential to enable an economic and ecological production of functional components through short process chains. SBMF from coil also provides additional advantages regarding high output quantity and short cycle times. However, the industrially application of SBMF from coil is limited due to high tool load and coil-specific challenges like an anisotropic material flow, which negatively affects the part accuracy. In this study, a backward extrusion process from coil for forming functional components with gearing is investigated. Therefore, a numerical process model was built and validated based on experimental results. In order to generate a profound process understanding, a combined numerical-experimental approach was chosen for a fundamental process analysis. The influence of the semi-finished product geometry was investigated by forming rotationally symmetric, pre-cut blanks and coil material. The application of the different sheet geometries was compared based on component- and process-side target quantities. The results indicate an anisotropic material flow as a coil-specific challenge, which leads to a direction-dependent component formin

Numerical and experimental investigation of extrusion processes from coil - Leicht, Miriam; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2024)
The use of coil material as semi-finished product in sheet-bulk metal forming (SBMF), offers the possibility to use high-speed presses and thus to achieve high output quantities. However, compared to industrially established forming of pre-cut blanks, the reduced geometric accuracy of the parts due to the asymmetrical material flow represents a challenge. Against this background, the aim of this study is to gain an in-depth knowledge on the influence of the process setup on the material flow direction and on the forming of geared functional parts. A combined numerical-experimental approach of each a lateral and a backward extrusion process of a DC04 sheet metal (t0 = 2 mm) is applied for a fundamental process analysis. For this purpose, process-dependent causes for the asymmetric part forming are analyzed by means of material flow simulations. Subsequently, the numerical results are verified experimentally in terms of the part geometry, the process force and grain structural changes. Based on the numerical and experimental results, cause-effect relations between material flow, part accuracy and tool load are derived. In addition, the transferability of the causes of the asymmetric material flow to processes with different primary material flow directions and part geometries is verified. The findings facilitate the future counteraction of asymmetrical material flow in SBMF from coil, which in turn leads to enhanced component quality.
CRIS-Team Scopus Importer:2024-09-27
Keywords: cold forming; extrusion; Sheet-bulk metal forming